Composite flexible film and preparation method and application thereof

By constructing a composite flexible film, using the combination of nano powder and bonding materials, the problems of poor dielectric performance and insufficient conductivity of the film capacitor are solved, and film capacitors with high dielectric constant, low internal resistance and low heat generation are achieved, which expands its application range.

CN119682358APending Publication Date: 2025-03-25HUNAN JURONG MATERIALS TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411519747.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The dielectric performance of existing film capacitors is poor, which makes it difficult to increase the capacitance and bias breakdown voltage, and the conductivity of metal electrodes is poor, resulting in large internal resistance and heating, limiting the long-term reliability and application range of film capacitors.

Method used

A composite flexible film is constructed by a sequentially stacked upper base film, high dielectric layer and lower base film. The nano powder in the high dielectric layer is dispersed in the binder to increase the dielectric constant, and an integral film is formed through a hot pressing process to improve breakdown resistance and flexibility.

Benefits of technology

It significantly improves the dielectric constant and capacity of film capacitors, reduces internal resistance and heating phenomena, improves the long-term reliability and application range of film capacitors, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119682358A_ABST
    Figure CN119682358A_ABST
Patent Text Reader

Abstract

The invention discloses a composite flexible thin film and a preparation method and application thereof, the composite flexible thin film can be used for manufacturing a thin film capacitor device, and the composite flexible thin film comprises an upper base film, a high dielectric layer and a lower base film which are laminated in sequence; the upper base film and the lower base film are made of organic film materials; and the high dielectric layer comprises nano powder and a binding material. The preparation method comprises the following steps: (1) dispersing nano powder into a binding material to obtain slurry; (2) coating the surface of a lower base membrane with the slurry, and drying to obtain an intermediate product; and (3) pressing the intermediate product and the upper base film by adopting a hot pressing process. According to the composite flexible film, the dielectric constant is 10.0-200.0, the surface roughness is smaller than 20 nm, the capacitance of a film capacitor can be improved, a continuous and compact conductive layer is formed on the surface through evaporation, the internal resistance of the film capacitor is reduced, the heating phenomenon of the film capacitor is relieved or even avoided, the preparation process is simple, and the composite flexible film is suitable for large-area and high-energy preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of dielectric materials, and in particular to a composite flexible film and a preparation method and application thereof. Background Art

[0002] Film capacitors are capacitors that use metal as their electrodes. They need to combine metal electrodes with various organic films with different dielectric constants, such as polyethylene, polypropylene, polystyrene, and polycarbonate. Since the dielectric constant of organic film materials is generally low, it is difficult to achieve major breakthroughs in capacitance and partial breakdown voltage. In addition, the poor conductivity of metal electrodes leads to a large internal resistance of film capacitors, and the heat generation during use also restricts the long-term reliability of film capacitors.

[0003] Chinese patent 201811229579.3 provides a polypropylene / high dielectric constant composite material for capacitors, which increases the dielectric constant of polypropylene from 2.3 to 2.7. However, the process of preparing the two-dimensional ceramic masterbatch by mixing will cause the flexibility of the polypropylene film to decrease; Chinese patent 202010010849 .2 provides a polypropylene double-layer film for capacitors, using a simple polyurethane-based composite material coating to increase the dielectric constant of polypropylene to 2.5; Chinese patent 202111174203.9 provides a polypropylene capacitor film and a preparation method thereof, and a polyvinyl alcohol-based composite material coating is coated on the polypropylene film. As can be seen from Example 6, the maximum dielectric constant is 4.10; although the above-mentioned technology has improved the dielectric properties of the film material to a certain extent, it is affected by the properties of the material itself. Even after improvement, the dielectric constant of the organic film material is generally still below 5, and it is also unable to significantly improve and enhance the use effect of the film capacitor; Chinese patent 201510478697.8 provides a polypropylene-based composite dielectric film blended with nano-ceramic powder for film capacitors and a preparation method thereof, which is made of a nanocrystalline cellulose / polyvinylidene fluoride composite coating blended with nano-ceramic powder, and has a dielectric constant of 350 at a frequency of 1 KHz under room temperature conditions.

[0004] In existing solutions, increasing the dielectric constant of the wound film through coating is considered to be the key to improving the overall performance of film capacitors. However, the conductivity of the electrode is easily overlooked. The coating generally has a high surface roughness (usually micrometer level), which will lead to quality problems of the electrode formed by vapor deposition on it. In the process of preparing capacitors, the quality of the vapor-deposited electrode is an important part of the electrode conductivity. Although it can be further compensated by using high-conductivity gold and silver as electrodes, or vapor-depositing thicker metals as electrodes, both will significantly increase the cost of the capacitor.

[0005] Therefore, developing a high dielectric constant film to increase the capacitor capacity and a low surface roughness film to reduce the heating of the capacitor is an effective means to promote the expansion of the application range of film capacitors and is also the key to the development and upgrading of film capacitor technology. Summary of the invention

[0006] The present invention provides a composite flexible film with high dielectric constant and low surface roughness, and a preparation method and application thereof, so as to solve the technical problems of poor dielectric performance and possible influence on electrode quality in the prior art mentioned in the background technology.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: A composite flexible film comprises an upper base film, a high dielectric layer and a lower base film which are stacked in sequence; the upper base film and the lower base film are both made of organic film materials; the high dielectric layer comprises nano powder and a binder.

[0008] The design idea of ​​the above technical solution is that the present invention constructs a composite flexible film with a sandwich structure through an upper base film, a high dielectric layer and a lower base film; in the high dielectric layer, nano powder materials are dispersed in a binder to improve the dielectric constant of the composite film and ensure the overall dielectric performance; the upper base film and the lower base film cover the surface of the high dielectric layer, which, on the one hand, serves as a flexible support for the overall film, and on the other hand, improves the breakdown resistance of the composite film, and avoids the reduction of the breakdown voltage when the gap is generated between the organic material and the inorganic material during the slitting, winding and other process operations in the capacitor preparation process. At the same time, the upper base film and the lower base film formed with organic film materials as raw materials have a low surface roughness, which avoids the adverse effects on the quality of electrode formation when the high dielectric layer with a high surface roughness is directly used as the film surface. When the nano-scale metal electrode is subsequently evaporated, it is easier to form a continuous and dense metal conductive layer, thereby preparing a low-cost high-conductivity electrode.

[0009] As a further preferred embodiment of the above technical solution, the organic film material includes one of a polyester organic film and a polypropylene organic film; and the surface roughness of the organic film material is less than 20 nm.

[0010] As a further preferred embodiment of the above technical solution, the nano powder includes at least one of barium titanate and barium strontium titanate, and the particle size D of the nano powder is 50 The dielectric constant of the nano powder is 100-500 nm, and the dielectric constant of the nano powder is 2000-5000. Selecting nano ceramic powder with a high dielectric constant can effectively improve the dielectric constant of the high dielectric layer and further improve the dielectric constant of the composite flexible film.

[0011] As a further preferred embodiment of the above technical solution, the binder includes at least one of water-based polyester or water-based polyurethane. The above binder can provide a certain degree of flexibility to the highly conductive layer and the film as a whole, and at the same time, the water-based material system is used to avoid the use of organic solvent systems such as ether, benzene, aldehyde, etc., which is more environmentally friendly.

[0012] As a further preferred embodiment of the above technical solution, the thickness of the upper base film and the lower base film are both 3.0-20.0 μm; and the total thickness of the composite flexible film is 10.0-50.0 μm.

[0013] As a further preferred embodiment of the above technical solution, the dielectric constant of the composite flexible film is 10-200.

[0014] Based on the same technical concept, the present invention also provides a method for preparing the above-mentioned composite flexible film, comprising the following steps: (1) dispersing the nanopowder in a binder to obtain a slurry; (2) coating the slurry on the surface of the lower base film and drying it to obtain an intermediate product; (3) The intermediate product and the upper base film are pressed together by a hot pressing process to form the composite flexible film.

[0015] As a further preferred embodiment of the above technical solution, after the nano powder is dispersed in the binder in step (1), a slurry is obtained by high-pressure homogenization, and the pressure of the high-pressure homogenization is 600-1200 MPa. The nano powder is dispersed in the organic binder, and a high pressure is obtained by a high-pressure pump. When the nano powder passes through the gap of the homogenization valve, it is crushed and emulsified by a strong shearing action due to the small gap. Compared with ultrasonic stirring, stirring dispersion, grinding dispersion, and lifting dispersion processes, the high-pressure homogenization process used in the present invention has a higher degree of dispersion.

[0016] As a further preferred embodiment of the above technical solution, after the nano powder is dispersed in the binder in step (1), the slurry is obtained by high pressure homogenization and filtration, and the mesh number of the filter is 600-1200 mesh. The slurry filtered through a specific filter is more uniform, which is conducive to coating a high dielectric layer with good uniformity.

[0017] As a further preferred embodiment of the above technical solution, the temperature of the hot pressing process in step (3) is 60-100°C and the pressure is 0.3-2MPa. Setting the hot pressing temperature below the Tg point of the upper base film, the high dielectric layer and the lower base film can avoid the material from curling and affecting the appearance of the film, and can also avoid the fluctuation of the dielectric constant after being subjected to high temperature.

[0018] Based on the same technical concept, the present invention also provides an application of the above-mentioned composite flexible film, and the composite flexible film is used to manufacture a thin film capacitor device.

[0019] As a further preferred embodiment of the above technical solution, when the composite flexible film is used to make a thin film capacitor device, the following steps are included: (1) evaporating a metal electrode on any surface of the composite flexible film and dividing it into pieces of set width to obtain a film roll; (2) Winding the film into a capacitor preparation material; (3) Leading out the positive and negative electrodes at both ends of the capacitor preparation material; (4) The capacitor preparation material is pressed into a dense capacitor by high-pressure hot forming.

[0020] Compared with the prior art, the advantages of the present invention are: (1) The composite flexible film of the present invention has a dielectric constant of 10.0 to 200.0 and a surface roughness of less than 20 nm. When used to make thin film capacitor devices, it can significantly increase the capacitance of the thin film capacitor. A continuous and dense conductive layer can be formed on the surface of the film by vapor deposition, thereby reducing the internal resistance of the thin film capacitor and alleviating or even avoiding the heating phenomenon of the thin film capacitor.

[0021] (2) The composite flexible film preparation process of the present invention is simple and suitable for large-area and high-energy preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 is a schematic structural diagram of the composite flexible film of Example 1; Figure 2 This is a photo of the composite flexible film of Example 1; Figure 3 This is a SEM image of the metal electrode formed by vapor deposition on the surface of the composite flexible film of Example 1; Figure 4 This is a photograph of the capacitor preparation material wound up from the composite flexible film of Example 1. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with specific embodiments.

[0025] Embodiment 1: like Figure 1 and Figure 2 As shown ( Figure 11 is a lower base film, 2 is an upper base film, 3 is a binder, and 4 is a nano powder). The composite flexible film with high dielectric constant and low surface roughness of this embodiment has a total thickness of 10 μm, a dielectric constant of 20.0, and a dielectric loss tangent of less than 0.001, and includes an upper base film, a high dielectric layer and a lower base film stacked in sequence, wherein the upper base film and the lower base film are selected from polyester organic films, each with a thickness of 3.0 μm and a surface roughness of less than 20 nm, the high dielectric layer includes a binder and nano powders dispersed in the binder, the binder is a water-based polyester resin (BASF, C88A), the nano powder is barium titanate, and the particle size D of the barium titanate is 0.1747 W. 50 It is 150nm and the dielectric constant is 2000.

[0026] The method for preparing the composite flexible film with high dielectric constant and low surface roughness of this embodiment comprises the following steps: (1) Dispersing barium titanate in aqueous polyester, subjecting it to high-pressure homogenization and filtering, to obtain a slurry; the pressure of the high-pressure homogenization is 800 MPa; the mesh size of the filter is 600 mesh; (2) coating the slurry on the surface of the lower base film and drying it to obtain an intermediate product; (3) The intermediate product and the upper base film are pressed together by a hot pressing process to form the composite flexible film of this embodiment; the hot pressing temperature is 80° C. and the hot pressing pressure is 1 MPa.

[0027] After evaporating a metal electrode on any side of the composite flexible film of this embodiment (the SEM image of the metal electrode is as shown in FIG. Figure 3 As shown in the figure, it is a continuous, dense and uniform morphology structure), cut into strips with a width of 40 mm and a length of 2800 mm. The cut film is wound into Figure 4 The capacitor pre-material shown in the figure has positive and negative electrodes drawn out by gold spraying at both ends, and then is pressed into a dense film capacitor by high-pressure hot forming. Tested under 1KHz frequency conditions, the capacity is 98.9 nF, the loss is 0.032, and the temperature change is less than 5°C after 200 hours of continuous operation, achieving the expected goal.

[0028] Embodiment 2: The composite flexible film with high dielectric constant and low surface roughness of the present embodiment has a total thickness of 50 μm, a dielectric constant of 200.0, and a dielectric loss tangent of less than 0.001, and comprises an upper base film, a high dielectric layer and a lower base film which are stacked in sequence, wherein the upper base film and the lower base film are polypropylene organic films, each having a thickness of 20.0 μm and a surface roughness of less than 20 nm, the high dielectric layer comprises a binder and nano powders dispersed in the binder, the binder is water-based polyurethane resin (BASF, C85A), the nano powder is barium strontium titanate, and the particle size D of barium strontium titanate is 1.34 mm. 50 It is 500nm and the dielectric constant is 5000.

[0029] The method for preparing the composite flexible film with high dielectric constant and low surface roughness of this embodiment comprises the following steps: (1) Dispersing barium titanate in aqueous polyester, subjecting it to high-pressure homogenization and filtering, to obtain a slurry; the pressure of the high-pressure homogenization is 600 MPa; the mesh size of the filter is 600 mesh; (2) coating the slurry on the surface of the lower base film and drying it to obtain an intermediate product; (3) The intermediate product and the upper base film are pressed together by a hot pressing process to form the composite flexible film of this embodiment; the hot pressing temperature is 100° C. and the hot pressing pressure is 2 MPa.

[0030] After the metal electrode is evaporated on any side of the composite flexible film of this embodiment, it is cut into strips with a width of 40 mm and a length of 2800 mm. The cut film is wound into a capacitor preparation material, and the positive and negative electrodes are drawn out by gold spraying at both ends. Then, the preparation material is pressed into a dense film capacitor by high-pressure hot forming. Tested under 1KHz frequency conditions, the capacity is 152.3 nF, the loss is 0.041, and the temperature change is less than 6 °C after 200 hours of continuous operation, achieving the expected goal.

[0031] Embodiment 3: The composite flexible film with high dielectric constant and low surface roughness of the present embodiment has a total thickness of 25 μm, a dielectric constant of 650.0, and a dielectric loss tangent of less than 0.001, and comprises an upper base film, a high dielectric layer and a lower base film stacked in sequence, wherein the upper base film and the lower base film are polypropylene organic films, each with a thickness of 10.0 μm and a surface roughness of less than 20 nm, the high dielectric layer comprises a binder and nanopowders dispersed in the binder, the binder is water-based polyurethane resin (BASF, C88A), the nanopowder is barium titanate, and the particle size D of the barium titanate is 0.1747 W / cm2. 50 It is 100nm and the dielectric constant is 3000.

[0032] The method for preparing the composite flexible film with high dielectric constant and low surface roughness of this embodiment comprises the following steps: (1) Dispersing barium titanate in aqueous polyester, subjecting the mixture to high-pressure homogenization and filtration to obtain a slurry; the pressure of the high-pressure homogenization is 1200 MPa; the mesh size of the filter is 1200 mesh; (2) coating the slurry on the surface of the lower base film and drying it to obtain an intermediate product; (3) The intermediate product and the upper base film are pressed together by a hot pressing process to form the composite flexible film of this embodiment; the hot pressing temperature is 60° C. and the hot pressing pressure is 0.3 MPa.

[0033] After the metal electrode is evaporated on any side of the composite flexible film of this embodiment, it is cut into strips with a width of 40 mm and a length of 2800 mm. The cut film is wound into a capacitor preparation material, and the positive and negative electrodes are drawn out by gold spraying at both ends. Then, the preparation material is pressed into a dense film capacitor by high-pressure hot forming. Tested under 1KHz frequency conditions, the capacity is 263.2 nF, the loss is 0.037, and the temperature change is less than 5°C after 200 hours of continuous operation, achieving the expected goal.

[0034] Comparative Example 1: The difference between the thin film capacitor of this comparative example and Example 1 is that the metal electrode of this comparative example is directly evaporated on the same lower base film as Example 1, without an upper base film and an intermediate high dielectric layer. Other parameters and conditions are the same as Example 1.

[0035] Comparative Example 2: The difference between the thin film capacitor of this comparative example and Example 1 is that the composite thin film of this comparative example is obtained by coating the slurry obtained in step (1) of Example 1 on the surface of the lower base film and drying it to obtain an intermediate product, and directly vapor-depositing a metal electrode on the intermediate product without involving the upper base film. Other parameters and conditions are the same as those of Example 1.

[0036] Comparative Example 3: The difference between the film capacitor of this comparative example and Example 1 is that when preparing the composite film in this comparative example, the hot pressing temperature of step (3) is adjusted to 40° C., and the other parameters and conditions are the same as those in Example 1.

[0037] Table 1 Performance test results of film capacitors of various embodiments and comparative examples

[0038] As can be seen from Table 1, the dielectric constant of the composite flexible film obtained by the present invention can be increased from 2.3 of the single-layer base film to 650.0, and the dielectric constant is significantly improved. The performance comparison of the internal resistance of Examples 1-3 and Comparative Example 1 with that of Comparative Example 2 shows that the internal resistance of the metal electrode prepared on the base film (14.7 - 16.4 mΩ) is lower than that of the metal electrode prepared on the high dielectric layer (54.3 mΩ). Furthermore, the capacity of the film capacitor prepared by the composite flexible film with a high dielectric layer (Examples 1-3, Comparative Example 2) is higher than that of the film capacitor without a high dielectric layer (Comparative Example 1). In addition, the comparison of the dielectric loss between Example 1 and Comparative Example 3 shows that if the hot pressing temperature is not enough, the air inside the film capacitor will not be removed cleanly, resulting in a larger dielectric loss value.

[0039] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A composite flexible film, characterized in that: It comprises an upper base film, a high dielectric layer and a lower base film which are stacked in sequence; the upper base film and the lower base film are both made of organic film materials; the high dielectric layer comprises nano powder and a binder.

2. The composite flexible film according to claim 1, characterized in that: The organic film material comprises one of a polyester organic film and a polypropylene organic film; and the surface roughness of the organic film material is less than 20 nm.

3. The composite flexible film according to claim 1, characterized in that: The nano powder includes at least one of barium titanate and barium strontium titanate, and the particle size D of the nano powder is 50 The diameter of the nanopowder is 100-500 nm, and the dielectric constant of the nanopowder is 2000-5000.

4. The composite flexible film according to claim 1, characterized in that: The binder includes at least one of a water-based polyester resin or a water-based polyurethane resin.

5. The composite flexible film according to any one of claims 1 to 4, characterized in that: The thickness of the upper base film and the lower base film are both 3.0-20.0 μm; the total thickness of the composite flexible film is 10.0-50.0 μm, and the dielectric constant of the composite flexible film is 10-200.

6. A method for preparing the composite flexible film according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) dispersing the nanopowder in a binder to obtain a slurry; (2) coating the slurry on the surface of the lower base film and drying it to obtain an intermediate product; (3) The intermediate product and the upper base film are pressed together by a hot pressing process to form the composite flexible film.

7. The method for preparing a composite flexible film according to claim 6, characterized in that: In step (1), the nanopowder is dispersed in the binder and then subjected to high-pressure homogenization to obtain a slurry, wherein the pressure of the high-pressure homogenization is 600-1200 MPa.

8. The method for preparing a composite flexible film according to claim 7, characterized in that: In step (1), the nano powder is dispersed in the binder, and then subjected to high pressure homogenization and filtration to obtain a slurry, wherein the mesh size of the filter is 600-1200 meshes.

9. The method for preparing a composite flexible film according to any one of claims 6 to 8, characterized in that: The temperature of the hot pressing process in step (3) is 60-100°C and the pressure is 0.3-2MPa.

10. Use of the composite flexible film according to any one of claims 1 to 5 or the composite flexible film prepared by the preparation method according to any one of claims 6 to 9, characterized in that: The composite flexible film is used to manufacture a thin film capacitor device; when the composite flexible film is used to manufacture a thin film capacitor device, the following steps are included: (1) evaporating a metal electrode on any surface of the composite flexible film and dividing it into pieces of set width to obtain a film roll; (2) Winding the film into a capacitor preparation material; (3) Leading out the positive and negative electrodes at both ends of the capacitor preparation material; (4) The capacitor preparation material is pressed into a dense capacitor by high-pressure hot forming.

Citation Information

Patent Citations

  • Nano-ceramic-powder-doped polypropylene-based composite dielectric film used for film capacitors and preparation method of nano-ceramic-powder-doped polypropylene-based composite dielectric film

    CN105037775A

  • High-energy-density polymer-based nano composite material and preparation method thereof

    CN109486000A

  • Polypropylene capacitor film and preparation method thereof

    CN113817268A

  • Compound ceramic film lamination high energy storage density capacitor and preparation method thereof

    CN102496457A

  • Production process of capacitor

    CN110136957A